Chinese Medicine in the United States: Historical Development and Growth - Liping Bu (Wolters Kluwer Health/LWW, 2023)
Chinese medicine is growing rapidly in the United States both as a field of research and in the daily treatment of illnesses. The popularity of Chinese medicine, particularly acupuncture, as a healing mechanism demonstrates American people's positive experience with Chinese medicine and their embracing it as an alternative to the mainstream Western biomedicine. Chinese medicine is an important part of the Alternative and Complementary Medicine or Integrated Medicine in the United States health system. It is increasingly used and covered by health insurance. Although Chinese medicine has been in the United States since colonial times, it was discriminated against by local authorities. However, things began to change in the 1970s when individual states gradually passed laws to legalize the practice of acupuncture as a healing mechanism. American public interest in Chinese medicine, particularly acupuncture, was aroused by the media's report of the "magic" power of acupuncture during President Nixon's visit to China. Non-Asians studied acupuncture in the following decades, which contributed to the establishment of acupuncture as a profession in the American health system. The history of Chinese medicine in the United States illustrates that Chinese and Asian immigrants promoted Chinese medicine in the communities, while Chinese American medical scientists who were trained in biomedicine played an important role in shaping the biomedical method of acupuncture research. This article investigates the changes of Chinese medicine in the United States, with a focus on acupuncture. Situating the discussion in a larger context of social and cultural changes, this study examines the contributions of Chinese immigrants and the popularity of acupuncture in the United States. It analyzes the development of acupuncture practice and research, the professional training in Chinese medicine, and American people's interest in using Chinese medicine as a reliable healing mechanism to many health problems, including chronic pain, cancer, and drug addictions.